﻿First presentation of sarcoidosis with severe obstructive sleep apnoea and epiglottic invilvement - ﻿Ahmed, M.; ﻿Sulaiman, I.; ﻿Rutherford, R.; Gilmartin, J.J. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Sarcoidosis of the upper respiratory tract (SURT) is rare but well documented. We present a patient whose first presentation with sarcoidosis was with dysphonia, upper airways obstruction and severe obstructive sleep apnoea (OSA) . Systemic steroids and hydroxycholoroquine led to improvement in phonation, endoscopic appearance and upper airway obstruction with significant improvement in Apnoea Hypopnoea Index (AHI) on polysomnography.